Optimalisasi Efektivitas Program MBKM: Sistem Monitoring Berbasis Lokasi dan Analisis aktivitas dengan TF-IDF - Tarigan, Ita Margaretta Br; Tarigan, Siti Jamilah Br; Ginting, Raheliya Br (Journal of Information System Research (JOSH), 2024)
The research is based on the importance of a monitoring system for students who study outside the classroom which is very necessary on an ongoing basis, considering that the PT and DPL coordinators must continue to monitor directly or indirectly students who participate in MBKM activities. The problem so far has been the difference between the MBKM plan and the MBKM results, where from the monitoring results, there are several weaknesses in the information and data in the MBKM program, for example, difficulty in knowing the location. This study aims to design a location-based student activity monitoring system to make it easier for PT and DPL coordinators to find out student activities and make assessments based on the history of activities outside the classroom with the MBKM program followed by students. The activity history reported each day will be processed using the Term Frequency-Inverse Document Frequency (TF-IDF) method to find similarities in activities based on the completion time and types of activities carried out by students. The results of the activity history processed with TF-IDF are in the form of reports which will later become supporting information for objective assessment of student learning outcomes. The system design method used in this study is the Web Development Life Cycle (WDLC). The design stages in WDLC start from Planning, Analysis, Design and Development, Testing and Implementation and Maintenance. On the backend side for data management and reporting, a web-based system will be built with the PHP programming language using the YII2 PHP Framework. On the frontend side used by students is a mobile-based application (android) which will be built using the Ionic Framework. Data storage media uses MariaDB. The results of this study are a system that allows for monitoring students who study outside the classroom, especially students who participate in MBKM activities based on the history of activities reported at any time. Given the rapid development of technology and information today, the author suggests that it is necessary to develop the system, especially in terms of user interface, system availability in the form of applications (Android and iOS), and also increasing security, especially in terms of reading the location of student activities. The results of the test with the query Introduction to the environment, a visit to the village head's office to discuss future work programs obtained the results of the similarity level in Salsabilah Yahnun Fadila (21040203) which is 1%, Juliana Br Harianja (21040210) which is 0.7164%, Agung Dermansyah Nainggolan (21040257) which is 0.5978%, Lisman Buulolo (22090041) which is 0.4004% and Irwan Jaya Bawamenewi (21100251) which is 0.3645%. The time needed for this classification is 2.2471 minutes. For testing with the query Participating in community service activities/mutual cooperation, the results of the similarity level in Kristina Tutiniwati Ndruru (21100187) were 0.6111%, Alviusman Harita (21040253) was 0.5593%, Friska Sariaman Manalu (22070012) was 0.4735%. The time required for this classification was 1.2344 minutes.